Stabilizing Zinc Anodes by Regulating the Electrical Double Layer with Saccharin Anions. Issue 38 (2nd August 2021) - Huang, Cong; Zhao, Xin; Liu, Shuang; Hao, Yisu; Tang, Qunli; Hu, Aiping; Liu, Zhixiao; Chen, Xiaohua
Abstract: Zn anodes suffer from poor Coulombic efficiency (CE) and serious dendrite formation due to the unstable anode/electrolyte interface (AEI). The electrical double layer (EDL) structure formed before cycling is of great significance for building stable solid electrolyte interphase (SEI) on Zn surface but barely discussed in previous research about the stabilization of Zn anode. Herein, saccharin (Sac) is introduced as electrolyte additive for regulating the EDL structure on the AEI. It is found that Sac derived anions are preferentially adsorbed on the Zn metal surface instead of water dipole, creating a new H2 O‐poor EDL structure. Moreover, the unique SEI is also detected on the Zn surface due to the decomposition of Sac anions. Both are proved to be capable of modulating Zn deposition behavior and preventing side reactions. Encouragingly, Zn|Zn symmetric cells using Sac additive deliver a high cumulative plated capacity of 2.75 Ah cm −2 and a high average CE of 99.6% under harsh test condition (10 mA cm −2, 10 mAh cm −2 ). The excellent stability is also achieved at a high rate of 40 mA cm −2 . The effectiveness of this Sac additive is further demonstrated in the Zn‐MnO2 full cells. Abstract : Saccharin is introduced as an electrolyte additive for building a H2 O‐poor electrical double layer (EDL) structure near the Zn metal surface. With the presence of this unique EDL structure, Zn symmetric cells display a high cumulative plating capacity of 2.75 Ah cm −2 and a high average Coulombic efficiency (CE) of 99.6% under harsh test conditions (10 mA cm −2, 10 mAh cm −2 ).